Knowledge and uptake of occupational post-exposure prophylaxis amongst nurses caring for people living with HIV - Lufuno Makhado; Mashudu Davhana-Maselesele (AOSIS, 2016)
Background: Nurses caring for people living with HIV (PLWH) are at higher risk of exposure to the human immunodeficiency virus (HIV) by needle sticks, cuts, getting body fluids in their eyes or mouth and skin when bruised or affected by dermatitis. Objectives: To determine knowledge, insight and uptake of occupational post-exposure prophylaxis (OPEP) amongst nurses caring for PLWH. Method: A cross-sectional descriptive design was used in this study. Stratified random sampling was used to sample 240 nurses. The study was conducted in a regional hospital in Limpopo province. Both parametric and non-parametric statistics were employed to analyse data. Results: A total of 233 nurses participated in the study. Sixty per cent (n = 138) of all nurses had a situation at work when they thought that they were infected by HIV and 100 (43%) nurses had experienced the situation once or more in the past 12 month. Approximately 40% did not know what PEP (post-exposure prophylaxis) is, and 22% did not know or were not sure if it was available in the hospital. Only few participants (n = 68, 29%) had sought PEP and most (n = 37, 54%) of them did not receive PEP when they needed it. There was a significant association between the knowledge and availability of PEP (r = 0.622). Conclusion: The study recommend an urgent need for policy makers in the health sector to put in place policies, guidelines and programmes that will rapidly scale up PEP services in health care settings, so that preventable occupationally acquired HIV infection can be minimised amongst nurses. Keywords: Post-Exposure Prophylaxis; Nurses; HIV, Occupational Exposure; PLWH